A luminescent edge-interlocked prismatic heteroleptic metallocage assembled through a ligand replacement reaction - Zhan, Shun-Ze; Li, Jing-Hong; Zhang, Guo-Hui; Liu, Xiao-Wei; Li, Mian; Zheng, Ji; Ng, Seik Weng; Li, Dan (Royal Society of Chemistry, 2019)
A luminescent edge-interlocked heteroleptic metallocage based on Cu3(pyrazolate)3 was prepared through a ligand replacement reaction from a homoleptic metallocage and a new ligand. Its structure was confirmed by XRD and MALDI-TOF mass spectrometry. Theoretical calculations revealed the new ligand was evidently responsible for the bathochromic shift of the optimal excitation. This work provides a heteroleptic strategy to regulate the interlocking fashion and photophysical mechanism of metallocages based on Cu3(pyrazolate)3.